A ANALISIS DEFECT PADA PROSES PEMBUATAN KAYU LAPIS DENGAN METODE STATISTICAL PROCESS CONTROL (SPC) DAN ROOT CAUSE ANALYSIS (RCA) - Ismuka Aliyadi Sidikiyah (JUSTI (Jurnal Sistem dan Teknik Industri), 2022)
As a society, we need good products, both producers who sell and consumers who buy want their products to be of the expected quality. Conversely, if the quality of the product is not good, it will harm many parties and the bad impact received will not be small. That's why consumer satisfaction is very influential for the company, where consumers can make an assessment and grow confidence in a product that is produced especially plywood products. This study aims to determine the type of defect and its control using the Statistical Process Control (SPC) method. Statistical process control is a decision-making method for monitoring, controlling, analyzing, managing, and improving products and processes using statistical methods with the aid of histograms, Pareto charts, control charts, and fishbone diagrams. Based on the Pareto diagram, the most common product defects are over-sanding defects with a percentage of 46%, followed by under-size defects at 29.6%, and delamination at 24.4%. The main cause of defects in plywood products is the human factor because the operator is new to machine understanding and lacks training, the machine factor is caused by too many targets and a lack of human resources, and the method factor is due to the operator's lack of knowledge about sandpaper